Radiographic measurement of tibial joint angles in sheep - Hette, K; Rahal, S.C; Volpi, R.S; Pereira-Junior, O.C.M; Mamprim, M.J; Silva, V. Colombi da (Veterinary and comparative orthopaedics and traumatology, 2009)
The aim of this study was to establish normal reference values of anatomic and mechanical joint angles of the tibia in sheep at different age groups. Eighteen clinically healthy Santa Ines sheep were used. The animals were divided into three equal groups according to age: Group I - from six- to eight-months-old, Group II - 2-years-old, Group III - from three- to five-years-old. Anatomic medial proximal and lateral distal tibial angles, mechanical proximal and distal tibial angles, and anatomic caudal proximal and anatomic cranial distal tibial angles were measured from tibiae radiographs (n = 36). In the craniocaudal view, the mean values of the anatomic medial proximal, anatomic lateral distal, mechanical medial proximal, and mechanical lateral distal tibial joint angles were 89.6 masculine, 86.6 masculine, 91.4 masculine, and 85.19 masculine respectively. In mediolateral view, the mean values of the anatomic caudal proximal and anatomic cranial distal tibial angles were 64.55 masculine and 105.69 masculine, respectively. The joint orientation angles of the tibia in sheep showed similar values regardless of animal age for both anatomic and mechanical axes.